Meningkatkan Hafalan Al-Qur’an dengan Tutor Sebaya: Studi pada Q.S. Yunus 40-41 dan Q.S. Al-Ma’idah 32 - Hasibuan, Sehat; Lubis , Erita; Jubaidah , Siti (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aimed to investigate the impact of social media use on SD Negeri 011 Sungai Tapah. This study used a quantitative research method with a correlational research design. The sample of this study consisted of 100 student selected randomly. The research instrument was a questionnaire. The results showed a positive correlation between the frequency of using social media for learning and students’ academic achievement. However, the correlation between the duration of using social media for non-learning purposes and students’ academic achievement showed negative results. The conclusion of this study is that the use of social media can be an effective tool to improve students’ academic achievement if used appropriately and wisely.